Effect of the water exchange system on the development, survival, and performance of Argopecten purpuratus larvae culture (Pectinidae, Mollusca) - Luis Fernando Rios-Cruz; Guillermo Odilon Alvarez Bejar; Eric Hanschke Dileo (Ciencias Marinas)
Scallop cultivation on the coasts of Peru and Chile is continuously expanding, leading to increased larval production and the mounting need to enhance efficiency to boost sector productivity. This study focused on investigating how the water exchange system affects the development, survival, and performance of Argopecten purpuratus larvae. Three static water exchange systems (T1 [12-h exchange], T2 [24-h exchange], and T3 [48-h exchange]) and 2 recirculation systems (RAS 1 and RAS 2) were evaluated, with 3 replicates per treatment. The feed supplied in each treatment consisted of a mixture of the microalgae Isochrysis galbana, Diacronema lutheri, Chaetoceros calcitrans, Chaetoceros gracilis, and Nannochloropsis sp. at a concentration of 5 × 104 cell·mL–1·d–1. The results showed that survival was higher in T1 (80.49%) than in T2 (68.49%) or T3 (67.17%); lower survival was observed in RAS 2 (52.94%) and RAS 1 (6.34%). Furthermore, T1 resulted in significantly greater growth (shell height: 192.2 ± 9.03 μm; growth rate: 3.7 μm·d–1) than that of T2 or T3. Although RAS 1 was discarded due to high mortality, RAS 2 showed similar performance to that of T1 with regard to larval growth. Considering commercial factors and energy efficiency, T2 and T3 yielded the most favorable results in terms of larval survival and growth.